Is the Environmental, Social and Corporate Governance (ESG) score the missing factor in the Fama-French five factor asset pricing model? - Nsibande, Luyanda Malusi Qiniso (My University, 2022)
Background: Companies are increasingly encouraged to focus on the creation of sustainable value. In South Africa, financial research institutions evaluate and track companies’ performance based on environmental, social and governance-related criteria. These scores are intended to inform decisions by potential equity investors, amongst others. However, commonly-used asset pricing models do not include ESG scores. Purpose: The purpose of this research is to discover whether the inclusion of Environmental, Social and Governance (ESG) scores in the Fama and French fivefactor model (FF5) will improve the model’s predicting power of expected returns on the Johannesburg stock exchange JSE Methodology: For the largest 40 JSE-listed companies, statistical ordinary least squares (OLS) regression was employed with R statistics to analyse fundamental, share price and ESG score data over the five-year time period from 2015 to 2019. The researcher compared the predictive power of the FF5 model to that of the same model including ESG scores. Findings: The results showed that the predictive power of the FF5 model is only marginally improved when the ESG scores are incorporated. These findings may indicate that equity prices are not significantly influenced by ESG scores. Implications: The findings of this research provide the basis for further endeavours on the share-price implications of ESG performance. It makes a theoretical contribution by suggesting possible enhancements to traditional asset pricing techniques.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce in Accountancy to the Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2022
Keywords: UCTD; Environmental; Social and governance (ESG); Fama-French Five-Factor Model; JSE; SDG-8: Decent work and economic growth